Weak central coherence in neurodevelopmental disorders: a comparative study - Gambra, Leyre; Magallon, Sara; Crespo-Eguílaz, Nerea (Frontiers in Psychology, 2024)
Introduction: central coherence is the normal tendency to process and give meaning to incoming information taking into account the context or global view of that information. Methods: we assessed the central coherence of 252 schoolchildren of normal intelligence between 6 and 11 years old. We compared the performance of two groups: a) a control group (n=194), and b) a clinical group (n=58) comprising children with NVLD+ADHD (n=24), ADHD alone (n=16), SCD (n=8) and level-1ASD (n=10) (Kluskall-Wallis H and Mann-Whitney U were calculated to make comparisons within groups and between pairs of groups). The effects of medication were studied (Student's t test). Results: The NVLD+ADHD, SCD and ASD1 groups showed weak central coherence. The performance of the ADHD group was normal and differed significantly from the NVLD+ADHD group. Conclusion: central coherence deficit was not exclusive to ASD1: it also characterizes NVLD and SCD.